Turismo de Base Comunitária na Comunidade Kalunga do Engenho II em Cavalcante/GO: Perspectivas e Possibilidades - Costa, Pedro Almeida (2024)
The present study seeks to analyze the potential of community-based tourism (CBT) in the Kalunga community of Engenho II, highlighting its strategic location near the city of Cavalcante, in Goias, and its distinct cultural characteristics. The general objective of the study is to analyze the prospects for community-based tourism in the Kalunga community of Engenho II, located in Cavalcante/GO. The research was carried out through bibliographic analysis and fieldwork, with a qualitative, descriptive, and exploratory nature. The practice of CBT is contextualized as a multidimensional tourist activity, in which visitors seek recreation, rest, culture, and health outside their usual places of residence. CBT can play a role as a catalyst for socioeconomic development in regions with natural potential, such as the Brazilian savannah, offering opportunities for ecotourism, adventure tourism, and rural tourism. From the perspective of CBT, the community is placed at the center of planning, implementation, and monitoring of tourism activities, aiming to ensure equitable benefits and environmental preservation. The importance of ethical and sustainable approaches is emphasized, especially in historically marginalized communities like the Kalunga, where the preservation of cultural identity is prioritized. Furthermore, there is a need to combat racial fetishization and structural racism in cultural tourism, ensuring that black communities control their own narratives, a goal that can be achieved through Afro-entrepreneurship. In summary, CBT aims at cultural preservation and combating ethnic-racial inequalities, highlighting the importance of community leadership and respect for cultural autonomy. The involvement of the host community is fundamental for the successful implementation of this kind of tourism, ensuring cultural continuity and valorization. After visiting the Kalunga community of Engenho II and analyzing the experiences shared by the Kalunga people, it becomes evident that their quilombola identity is characterized by a strong connection to the land, historical resilience, and pride in their cultural roots, with resistance standing out as a prominent feature. Tourism emerges as an opportunity for economic and social development, contributing not only to income generation but also to cultural preservation. However, it is crucial that tourism be conducted in a participatory and respectful manner, considering the needs and aspirations of the local community.